Monitoring of Photonic-Crystal Fibers Positioning in the Connection Process - Filipenko, A.; Sychova, O. (ХНУРЭ, 2008)
In this report the monitoring method of PCF positioning at the connection process is offered. It is based on the matched filtration principle in the form of autoconvolution. Equations which connected PCF core axis coordinates with the maximum value of optical field intensity autoconvolution was obtained. It is shown that optical fiber displacement relatively base coordinates corresponds to half coordinates of autoconvolution maximum. Researches have shown that the offered method possesses high noiseproof factor and much higher accuracy in comparison with an integrated method.
Keywords: autoconvolution; connect; optical intensity distribution; photonic crystal fiber (PCF)